Design Improvement of a Semi-submersible Floating Offshore Wind Turbines through Frequency-domain Load Analyses - Soo Bin Lee; Joonmo Choung (한국해양공학회지)
The purpose of this study is to analyze the differences in motion response performances according to the design variables of semi-submersible substructures supporting floating offshore wind turbines (FOWTs) and propose an improved design. The specifications of the IEA 15 MW reference semi-submersible FOWT were used for this study. Draft, circumradius, main column diameter, and pontoon breadth were determined as dominant design variables that significantly affect the motion response of the substructure. A Python code was developed to automatically generate hundreds of analysis models. Motion responses were derived through frequency domain load analyses. The responses were heave natural period, pitch angle, and acceleration at the rotor nacelle assembly (RNA) with 20 year-return period. Deeper drafts resulted in less development of RNA acceleration and pitch angle. The main column diameter had the greatest impact on the heave natural period. Main column diameter, pontoon breadth, and circumradius controlled the pitch angle response amplitude operator (RAO) and RNA acceleration RAO. The RNA acceleration did not show consistent trends with design variables due to resonance. With assumed weighting factors for each variable, the reference FOWT substructure was improved. The results are expected to make a significant contribution to improving the motion performance of FOWTs.